2023
DOI: 10.1021/acs.langmuir.2c03341
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Organically Modified Silica for the Superhydrophobic Surface with Low Sliding Angle

Abstract: Extremely water-repellent surfaces with low sliding angle (SA) have been obtained with a facile single-step sol–gel strategy via co-condensation of tetraethoxysilane (TEOS) and hexadecyltrimethoxysilane (HDTMS) in basic media with an efficient self-cleaning property. We investigated the effect of the molar ratio of HDTMS and TEOS on the properties of the modified silica-coated poly­(ethylene terephthalate) (PET) film. A high water contact angle (WCA) of 165° and a low SA of 1.35° were obtained at a molar ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Aminosilane-modi ed silicate (Ormosil) is an organic-inorganic hybrid material formed by hydrolysis and condensation of organic-modi ed silane and alkoxide precursor. Ormosil materials are an important area of research in materials science, as they have been found to have many promising applications in the elds of optics, electronics, mechanics, energy, environment, biology, and medicine [1][2][3][4]. Ormosils have been shown to be excellent hosts for the capture of metal nanoparticles due to their ability to act as stabilizers or surface-capping agents [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Aminosilane-modi ed silicate (Ormosil) is an organic-inorganic hybrid material formed by hydrolysis and condensation of organic-modi ed silane and alkoxide precursor. Ormosil materials are an important area of research in materials science, as they have been found to have many promising applications in the elds of optics, electronics, mechanics, energy, environment, biology, and medicine [1][2][3][4]. Ormosils have been shown to be excellent hosts for the capture of metal nanoparticles due to their ability to act as stabilizers or surface-capping agents [5,6].…”
Section: Introductionmentioning
confidence: 99%